2020
DOI: 10.12659/msm.925147
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 Promotes Metastasis and Serves as a Marker of Poor Prognosis in Non-Small Cell Lung Cancer

Abstract: Background Metastasis contributes to the high mortality rate of non-small cell lung cancer (NSCLC), and gaining a better understanding of its metastatic mechanisms would aid in initiating effective clinical treatment. Material/Method In this study, bioinformatics analyses of the GEO database and TCGA-LUAD were first used to identify the key node gene regulating NSCLC malignant progression. Further in vitro experiments, including wound healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Our results indicated that TPX2 promoted the cytoplasmic migration of ETS-1, which not only expands our understanding of the regulation mechanism of transcription factor activity, but also deepens our understanding of the cytoskeleton affecting the activity of cell signaling pathways. Some previous data showed that TPX2 could promote the invasion of cancerous cells by enhancing the expression of MMPs and our data provided a promising mechanism of TPX2's effect on MMPs (12,13).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our results indicated that TPX2 promoted the cytoplasmic migration of ETS-1, which not only expands our understanding of the regulation mechanism of transcription factor activity, but also deepens our understanding of the cytoskeleton affecting the activity of cell signaling pathways. Some previous data showed that TPX2 could promote the invasion of cancerous cells by enhancing the expression of MMPs and our data provided a promising mechanism of TPX2's effect on MMPs (12,13).…”
Section: Discussionsupporting
confidence: 59%
“…A high level of TPX2 has been detected in several kinds of human cancer, such as bladder cancer, breast cancer, HCC, and especially prostate cancer (9,10). Previous research has focused on the role of TPX2 in centrosome formation and cell mitosis, and TPX2 is closely related to microtubules (11,12). The microtubule system is not only the basis for maintaining the morphology of cells but is also key to the transport of materials within cells (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for these function, in various cancers can TPX2 also control bladder cancer cell's proliferation and invasion via TPX2-p53-GLIPR1 regulatory circuitry [41], regulate the PI3K/AKT signaling pathway to facilitate hepatocellular carcinoma [42], interactive with miRNA such as miR-485-3p [43], miR-361-5p [44], miR-335-5p [45], miR-216b [46] and so on. Zhou et al have veri ed that TPX2 can activate the epithelial-mesenchymal transition process and promote both the expression and activities of matrix metalloproteinase (MMP)2 and MMP9 in non-small cell lung cancer (NSCLC), which means TPX2 promotes the metastasis and malignant progression of NSCLC and could thus serve as a marker of poor prognosis in NSCLC [47].…”
Section: Discussionmentioning
confidence: 99%
“…Except for these function, in various cancers can TPX2 also control bladder cancer cell's proliferation and invasion via TPX2-p53-GLIPR1 regulatory circuitry [40], regulate the PI3K/AKT signaling pathway to facilitate hepatocellular carcinoma [41], interactive with miRNA such as miR-485-3p [42], miR-361-5p [43], miR-335-5p [44], miR-216b [45] and so on. Zhou et al have veri ed that TPX2 can activate the epithelial-mesenchymal transition process and promote both the expression and activities of matrix metalloproteinase (MMP)2 and MMP9 in non-small cell lung cancer (NSCLC), which means TPX2 promotes the metastasis and malignant progression of NSCLC and could thus serve as a marker of poor prognosis in NSCLC [46]. Some studies have con rmed that COL1A1-related miRNAs were involved in the regulation of different kinds of tumors, including LUAD [17,47].…”
Section: Discussionmentioning
confidence: 99%